Pembelajaran Matematika Berbasis STEM: Implementasi Variasi Pengembangan Model Pembelajaran STEM di Sekolah Dasar - Hardani Hardani (Pusat Pengembangan dan Pemberdayaan Pendidik dan Tenaga Kependidikan Matematika, 2020)
STEM is a learning approach that integrates science, technology, engineering and mathematics in the problem-solving based activities. The integration of the four scientific disciplines in STEM project activities uses the Engineering Design Process (EDP) stage. This stage is a cycle in the form of repeated steps and might change until a problem-solving solution is identified. The difference of elementary school students’ characteristics and stages of cognitive development as well as the absences of a specific STEM curriculum causes teachers who are new to STEM find it difficult in implementing the existing model. Therefore, it is necessary to develop the stages of the STEM learning model in accordance with the characteristics of teachers and students. This stage was developed with the aim of making STEM easier to apply and easily connecting problems with product development from the STEM project. The variation of the STEM learning model developed includes the stages: create, identify, ideate, plan, build, and communicate. The STEM Learning Model design developed will make it easier for teachers to implement STEM in classroom learning.